Pitfalls in Colombia’s adoption system - Muñoz-Gómez, Diana Sthefania (2022)
The adoption system in Colombia faces many challenges in the face of the high percentage of children who cannot be placed in a family. The purpose of this study was to analyze the pitfalls in the Colombian adoption system. The methodology used was based on theoretical-legal and empirical research. When inquiring about the main aspects of the adoption system we found that, despite the evolution of regulations and case law, the process is lengthy and difficult, thus many minors are institutionalized for a long time, thus many minors are institutionalized for a long time and potential adoptive families desist from adoption. Adoption is a choice based on love, on a deep conviction of welcoming a new member into the family; it is a measure to restore right and hence need to be addressed and prioritized by legal systems in general.